A global approach to crop wild relative conservation: securing the gene pool for food and agriculture - Maxted, Nigel; Kell, S.; Toledo, A.; Dulloo, Mohammad Ehsan; Heywood, V.; Hodgkin, T.; Hunter D; Guarino, Luigi; Jarvis, Andy; Ford-Lloyd, B.V. (Springer, 2010)
In light of the growing concern over the potentially devastating impacts on biodiversity and food security of climate change and the massively growing world population, taking action to conserve crop wild relatives (CWR), is no longer an option it is a priority. Crop wild relatives are species closely related to crops, including their progenitors, many of which have the potential to contribute beneficial traits to crops, such as pest or disease resistance, yield improvement or stability. They are a critical component of plant genetic resources for food and agriculture (PGRFA), have already made major contributions to crop production and are vital for future food security; their systematic conservation in ways that ensure their continuing availability for use is therefore imperative. This is a complex, interdisciplinary, global issue that has been addressed by various national and international initiatives. Drawing on the lessons learnt from these initiatives we can now propose a global approach to CWR conservation, the key elements of which are: (1) estimating global CWR numbers, (2) assessment of the global importance of CWR diversity, (3) current conservation status, (4) threats to CWR diversity, (5) systematic approaches to CWR conservation, (6) CWR informatics, and (7) enhancing the use of CWR diversity.